2008
DOI: 10.1128/jb.01509-07
|View full text |Cite
|
Sign up to set email alerts
|

Two Closely Related ABC Transporters in Streptococcus mutans Are Involved in Disaccharide and/or Oligosaccharide Uptake

Abstract: Streptococcus mutans has a large number of transporters apparently involved in the uptake of carbohydrates. At least two of these, the multiple sugar metabolism transporter, MsmEFGK, and the previously uncharacterized MalXFGK, are members of the ATP-binding cassette (ABC) superfamily. Mutation analysis revealed that the MsmEFGK and MalXFGK transporters are principally involved in the uptake of distinct disaccharides and/or oligosaccharides. Furthermore, the data also indicated an unusual protein interaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 41 publications
4
82
1
Order By: Relevance
“…including antibiotic resistance, nutrient acquisition, adhesion, protein secretion, environmental sensing, spore formation, conjugation, and growth under stress conditions (39). As a consequence, many ABC transporters have been shown by signature-tagged mutagenesis (STM) screens to be important for the virulence of a range of bacterial pathogens, including Yersinia spp., Staphylococcus aureus, and Streptococcus pneumoniae (9,15,22,26), and these data have been supported by publications on the functions of individual ABC transporters (6,7,38,45).…”
supporting
confidence: 49%
“…including antibiotic resistance, nutrient acquisition, adhesion, protein secretion, environmental sensing, spore formation, conjugation, and growth under stress conditions (39). As a consequence, many ABC transporters have been shown by signature-tagged mutagenesis (STM) screens to be important for the virulence of a range of bacterial pathogens, including Yersinia spp., Staphylococcus aureus, and Streptococcus pneumoniae (9,15,22,26), and these data have been supported by publications on the functions of individual ABC transporters (6,7,38,45).…”
supporting
confidence: 49%
“…In Streptococcus mutans, the MsmEFGK system transports raffinose, melibiose, and stachyose, and the MalXFGK transporter is specific for maltodextrins (32). The two ATPase domains, MsmK and MalX, were shown to interact with either transporter system to energize uptake (32). In B. subtilis it was previously shown that MsmX energizes MdxEFG, a transporter specific for maltodextrins, as the cognate ABC domain (27).…”
Section: Discussionmentioning
confidence: 99%
“…MsiK energizes the cellobiose, xylobiose, and maltose uptake systems in Streptomyces lividans (9,26), the trehalose uptake system in Streptomyces reticuli (25), and the N,NЈ-diacetylchitobiose uptake in Streptomyces coelicolor (21). In Streptococcus mutans, the MsmEFGK system transports raffinose, melibiose, and stachyose, and the MalXFGK transporter is specific for maltodextrins (32). The two ATPase domains, MsmK and MalX, were shown to interact with either transporter system to energize uptake (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, as the substrates are diverse in the types of monomer, bonding (␣-or ␤-glycosidic bonds), and degree of polymerization (disaccharides, trisaccharides, and probably oligosaccharides from the breakdown of starch and glycogen), the latter scenario is less possible. Indeed, the interactions of ATPase subunits with different membrane permeases to form individual ABC transporters were observed with Gram-positive bacteria (42)(43)(44).…”
Section: Resultsmentioning
confidence: 99%